A Neovascularized Left Atrial Mass - Rania Hammami; Leila Abid; Souad Mallek; Ilyes Kharrat; Mariem Ellouz; Mourad Hentati; Imed Frikha; Samir Kammoun (Case Reports in Medicine)
Background. The discovery of a large left atrial mass through echocardiography obliges the clinician to perform a differential diagnosis to distinguish tumor from thrombus. The neovascularization of the mass could be helpful to predict the type of the malformation and whether it is in favour of a vacular tumour rather than a thrombus . Observation. A 43-years-old man who had no cardiac antecedent reported that he have had dyspnea and palpitation since 10 months. The cardiac auscultation, revealed an irregular rhythm with diastolic murmur at the apex. The electrocardiogram showed an atrial fibrillation. The transthoracic echocardiography revealed a severe mitral stenosis with a huge left atrial mass, confirmed through transesophageal echocardiography. After 4 weeks of an efficient anticoagulant treatment, the mass was still persistent in the echocardiography. So we decided to resect the mass and to achieve a mitral valve replacement. The preoperative coronarography showed neovascularization among the mass and fistula from the circumflex artery. Considering the characteristic of the mass (neovascularization and resistance to anticoagulant), we strongly suspected a vascular tumor especially myxoma, but the histological exam revealed an organized thrombus. Conclusion. Coronary neovascularization is a specific sign for left atrial thrombus in mitral stenosis, but surgery is the best way to confirm diagnosis.